Null signal for the cosmic anisotropy in the Pantheon supernovae data - Hua-Kai Deng; Hao Wei (European Physical Journal C: Particles and Fields, 2018)
Abstract The cosmological principle assumes that the universe is homogeneous and isotropic on cosmic scales. There exist many works testing the cosmic homogeneity and/or the cosmic isotropy of the universe in the literature. In fact, some observational hints of the cosmic anisotropy have been claimed. However, we note that the paucity of the data considered in the literature might be responsible for the “found” cosmic anisotropy. So, it might disappear in a large enough sample. Very recently, the Pantheon sample consisting of 1048 type Ia supernovae (SNIa) has been released, which is the largest spectroscopically confirmed SNIa sample to date. In the present work, we test the cosmic anisotropy in the Pantheon SNIa sample by using three methods, and hence the results from different methods can be cross-checked. All the results obtained by using the hemisphere comparison (HC) method, the dipole fitting (DF) method and HEALPix suggest that no evidence for the cosmic anisotropy is found in the Pantheon SNIa sample.